The masochistic pleasures of sentimental literature - Noble, Marianne, 1968- (Princeton University Press, 2000)
For generations, critics have noticed in nineteenth-century American women's sentimentality a streak of masochism, but their discussions of it have over-simplified its complex relationship to women's power. Marianne Noble argues that tropes of eroticized domination in sentimental literature must be recognized for what they were: a double-edged sword of both oppression and empowerment. She begins by exploring the cultural forces that came together to create this ideology of desire, particularly Protestant discourses relating suffering to love and middle-class discourses of "true womanhood." She goes on to demonstrate how sentimental literature takes advantage of the expressive power in the convergence of these two discourses to imagine women's romantic desire. Therefore, in sentimental literature, images of eroticized domination are not antithetical to female pleasure but rather can be constitutive of it. The book, however, does not simply celebrate that fact. In readings of Warner's The Wide Wide World, Stowe's Uncle Tom's Cabin, and Dickinson's sentimental poetry, it addresses the complex benefits and costs of nineteenth-century women's literary masochism. Ultimately it shows how these authors both exploited and were shaped by this discursive practice. The Masochistic Pleasures of Sentimental Literature exemplifies new trends in "Third Wave" feminist scholarship, presenting cultural and historical research informed by clear, lucid discussions of psychoanalytic and literary theory. It demonstrates that contemporary theories of masochism--including those of Deleuze, Bataille, Kristeva, Benjamin, Bersani, Noyes, Mansfield--are more relevant and comprehensible when considered in relation to sentimental literature